Gestão de risco em cadeia de suprimentos global: um estudo multicasos entre os membros da cadeia da manga - Ferreira Neto, Josué (2012)
The purpose of this study is to understand how different members manage risk in the global supply chain. Through a multicase study in the chain of Brazilian mango export to the United States were investigated links supplier, exporter, importer and logistics operator. We developed a research protocol as suggested by Yin (2010) and adapt them to data collection tool semi-structured Christopher et al. (2011). From interviews with organizations supporting the research object, it has been selected sample of companies in which the phenomenon of risk management could be better observed. Based on the type of risk ratings compiled by Christopher et al. (2011), it is suggested a new organization of risk categories (demand, supply, and process control, and environmental sustainability). This paper presents a description of the mango export chain, as well as key risks and risk mitigation strategies employed by four members of the chain studied. As a rule of Sousa (2001), comparisons were made between the types of risk and mitigation strategies observed in the supply chain. Finally, the study showed that risk management is heterogeneous among members of the chain, the exporter is the most penalized by the result of the risk chain and collaboration is the main form observed mitigation.